2002
DOI: 10.1038/sj.bjc.6600514
|View full text |Cite
|
Sign up to set email alerts
|

Effects of patient selection on the applicability of results from a randomised clinical trial (EORTC 10853) investigating breast-conserving therapy for DCIS

Abstract: Selection of patients for randomised clinical trials may have a large impact on the applicability of the study results to the general population presenting the same disorder. However, clinical characteristics and outcome data on non-entered patients are usually not available. The effects of patient selection for the EORTC 10853 trial investigating the role of radiotherapy in breast conserving therapy for ductal carcinoma in situ have been studied, in an analysis of all patients treated for ductal carcinoma in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
20
0
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 29 publications
1
20
0
1
Order By: Relevance
“…19 However, a comparison of a subgroup of patients treated with lumpectomy followed by radiotherapy outside and inside the trial showed significantly worse 4-year local recurrence-free rates: 83% outside the trial versus 98% inside the trial (P = .03). 21 For eligible patients treated with breast-conserving surgery only outside the trial, the 4-year recurrence-free rate was 93%, compared with 89% for randomized patients (P = .45). 21 Neither the NSABP nor EORTC trial revealed a beneficial effect of radiotherapy on either distant recurrences or breast cancer-related mortality.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…19 However, a comparison of a subgroup of patients treated with lumpectomy followed by radiotherapy outside and inside the trial showed significantly worse 4-year local recurrence-free rates: 83% outside the trial versus 98% inside the trial (P = .03). 21 For eligible patients treated with breast-conserving surgery only outside the trial, the 4-year recurrence-free rate was 93%, compared with 89% for randomized patients (P = .45). 21 Neither the NSABP nor EORTC trial revealed a beneficial effect of radiotherapy on either distant recurrences or breast cancer-related mortality.…”
Section: Discussionmentioning
confidence: 99%
“…21 For eligible patients treated with breast-conserving surgery only outside the trial, the 4-year recurrence-free rate was 93%, compared with 89% for randomized patients (P = .45). 21 Neither the NSABP nor EORTC trial revealed a beneficial effect of radiotherapy on either distant recurrences or breast cancer-related mortality.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations